Influence of cation−π interactions to the structural stability of phycocyanin proteins: A computational study. (October 2022) - Breberina, Luka M.; Nikolić, Milan R.; Stojanović, Srđan Đ.; Zlatović, Mario V.
Abstract: The influences of cation−π interactions in phycocyanin proteins and their environmental preferences were analyzed. The number of interactions formed by arginine showed to be higher than those formed by the lysine in the cationic group, while histidine is comparatively higher than phenylalanine and N-terminal residue in the π group. Arg−Tyr and Arg−Phe interacting pairs are predominant among the various pairs analyzed. Cation−π interactions are distance-dependent and can be realized above a wider area above the π ring. We analyzed the energy contribution resulting from cation−π interactions using ab initio calculations. The energy contribution resulting from the most frequent cation−π interactions was in the lower range of strong hydrogen bonds. The results showed that, while most of their interaction energies lay ranged from − 2 to − 8 kcal/mol, those energies could be up to −12− 12 kcal/mol. Stabilization centers for these proteins showed that all residues found in cation−π interactions are important in locating one or more of such centers. In the cation–π interacting residues, 54% of the amino acid residues involved in these interactions might be conserved in phycocyanins. From this study, we infer that cation−π forming residues play an important role in the stability of the multiply commercially used phycocyanin proteins and could help structural biologists and medicinal chemists to design better and safer drugs. Graphical Abstract: Example of a multiple cation–π interactions for the allophycocyanin from phycobilisomes of Mastigocladus laminosus ga1 Highlights: This is the first study aimed at the cation− π interactions in interfaces of phycocyanin proteins. Computational analysis was performed to study the role of cation− π interactions and their environmental preferences. Ab initio energy calculations were performed. The study might contribute useful information regarding structural stability and future designs of novel protein–bioactive compound interactions.